Gender differences in the effect of grief reactions and burnout on emotional distress among clinical oncologists. Issue 23 (10th August 2016) - Granek, Leeat; Krzyzanowska, Monika K.; Nakash, Ora; Cohen, Michal; Ariad, Samuel; Barbera, Lisa; Levy, Rotem; Ben‐David, Merav
Abstract : BACKGROUND: The current study was conducted to examine gender differences in the effect of grief reactions and burnout on emotional distress among clinical oncologists. METHODS: The participants included a convenience sample of 178 oncologists from Israel (52 of whom were women) and Canada (48 of whom were women). Oncologists completed a questionnaire package that included a sociodemographic survey, the General Health Questionnaire, a burnout measure, and the Adult Oncologists Grief Questionnaire. To examine the effect of grief reactions and burnout on emotional distress while controlling for country and past depression within each gender, 2 hierarchical linear regression analyses were computed. RESULTS: Female oncologists reported significantly more grief responses to patient death (mean, 47.72 [standard deviation (SD), 8.71] and mean, 44.53 [SD, 9.19], respectively), more emotional distress (mean, 12.41 [SD, 4.36] and mean, 10.64 [SD, 3.99], respectively), and more burnout (mean, 2.59 [SD, 1.69] and mean, 1.84 [SD, 1.5], respectively). For both genders, higher levels of grief reactions were associated with greater emotional distress among those who reported high levels of burnout ( P <.001). However, for men, the association between grief reactions and emotional distress also was documented at moderate levels of burnout ( P <.001). CONCLUSIONS: Patient death is a regular part of clinical oncology. It is essential that oncologists be able to cope effectively with this aspect of their work. The findings of the current study highlight the need to take into account the cumulative stressors that oncologists contend with when designing supportive interventions. Gender differences in burnout, reactions to patient death, and emotional distress need to be addressed to ensure the best quality of life for oncologists and the best quality of care for their patients. Cancer 2016;122:3705‐14. © 2016 American Cancer Society . Abstract : The findings of the current study highlight the need to take into account the cumulative stressors that oncologists contend with when designing supportive interventions to help them cope with patient death. Gender differences in burnout, reactions to patient death, and emotional distress need to be addressed to ensure the best quality of life for oncologists and the best quality of care for their patients.